Repetition Indicating Form and Function - Hocking, Paul (HIPHIL Novum, 2020)
It has long been observed that the repetition of literary devices has been used in the Bible and other ancient Near Eastern literature for the purpose of structuring the text and connecting related pericopes. The work done more recently under the TAPJLA project, labels the structuring aspect of repetition: “Repetitions as markers of architecture.” Also, the innovative work of Moshe Kline suggests that literary repetition has been used systematically in two-dimensional structuring of the Torah. This paper builds on these insights, together with elements of my own thesis on the rhetoric of Leviticus. It models an inductive, synchronic case study of a literary unit (Leviticus 23), to show how repetitions have been used both in the form and in the function of the unit, for composition and for suasion.